Intervención psicopedagógica con el programa PIAAR-R para la atención en una niña con trastorno por déficit de atención, del segundo grado de la unidad educativa Emiliano Ortega Espinosa, periodo 2023 - Vivanco Armijos, Miguel Augusto (2023)
The present degree work denominated: Psychopedagogical intervention with the PIAAR-R program for the care of a girl with attention deficit disorder, of the second grade of the Emiliano Ortega Espinosa educational unit, 2023 term, had as objective to improve care through the PIAAR-R program in a girl with attention deficit disorder, from the second grade of the Emiliano Ortega Espinosa educational unit, period 2023. It was carried out under the qualitative approach, descriptive and cross-sectional, through a case study. The techniques and instruments used were: the semi-structured interview, the attention test (d2) and the pre- and post-test technique. The results obtained from the test establish that the student presents a low level of attention which directly affects her academic performance, with this problem the PIAAR-R program was planned and executed, resulting in the student achieving an average level of attention. It is concluded that the psychopedagogical intervention had a significant impact on the student's attention level.